Public Participation Affecting the Efficiency of Waste Management of Tha Nam Oi Muang Hak Subdistrict Municipality, Phu Yuak Khiri District, Nakhon Sawan Province - Inprasit , Nattapong; Ratanasuwanachart , Naiyana; Swangthong, Thanaporn (Journal of Dhamma for Life, 2025)
This research examines the impact of public participation on the effectiveness of solid waste management in Tha Nam Oi Muang Hak Municipality. Aims to study 1) public participation in waste management in Tha Nam Oi Muang Hak Subdistrict Municipality, 2) study the level of effectiveness of waste management of Tha Nam Oi Muang Hak Subdistrict Municipality, 3) study the relationship between public participation and the effectiveness of waste management of Tha Nam Oi Muang Hak Subdistrict Municipality, and 4) to propose guidelines for promoting public participation affecting the effectiveness of waste management of Tha Nam Oi Muang Hak Subdistrict Municipality. Data were collected using questionnaires from a sample of 360 residents living in the Tha Nam Oi Muang Hak Municipality, Phayuha Khiri District. The research findings are as follows: 1. Public participation in overall waste management is at a high level. 2. The effectiveness of overall waste management is at a moderate level. 3. The relationship between public participation and the effectiveness of waste management is as follows: participation in decision-making is at a high level, participation in operations is at a high level, participation in benefit-sharing is at the highest level, and participation in evaluation is at a moderate level. Participation in benefit-sharing has a relationship with the effectiveness of waste management. 4. Public participation that impacts the effectiveness of waste management shows that participation in benefit-sharing affects the effectiveness of waste management.